VALIDITAS DAN EFEKTIVITAS MODUL INTERAKTIF PENUNJANG PERKULIAHAN BAHASA INGGRIS UNTUK FISIKA DALAM MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS UNTUK FISIKA - Budiarta, I Nengah Edi; Wiradika, I.N.I; Mardana, I.B.P (Universitas Pendidikan Ganesha, 2023)
Low English skills can have an impact on various things related to students' academic progress. One of them is that students have difficulty accessing various international learning references written in English. This research aims to develop an interactive module to support English lectures for physics in the Physics Education Study Program, Ganesha University of Education. Development of interactive modules as a solution to provide adaptive and effective physics English lecture teaching materials to increase students' motivation in attending lectures. Specifically, the objectives of this research include 1) describing the validity of the interactive module being developed; 2) describe the level of practicality of the interactive module being developed; 3) describe the effectiveness of the interactive module developed in increasing student learning motivation. This research uses development research methods with the ADDIE model (Analysis, Design, Develop, Implement, Evaluation).